2015
DOI: 10.3109/07853890.2015.1031822
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk markers in patients with psoriatic arthritis: A meta-analysis of literature studies

Abstract: These findings could help to establish more specific CV prevention strategies in this clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 47 publications
2
31
0
2
Order By: Relevance
“…This principle now mentions the importance of considering comorbidities, which are frequent in PsA and need to be assessed and treated. In particular, cardiovascular diseases and metabolic syndrome appear more common in patients with PsA than in controls 18 19…”
Section: Resultsmentioning
confidence: 99%
“…This principle now mentions the importance of considering comorbidities, which are frequent in PsA and need to be assessed and treated. In particular, cardiovascular diseases and metabolic syndrome appear more common in patients with PsA than in controls 18 19…”
Section: Resultsmentioning
confidence: 99%
“…There is also an increased prevalence of subclinical atherosclerosis in patients with PsA 14 15. A recent meta-analysis confirmed an increased carotid intima-media thickness (IMT) (mean difference: 0.07 mm, p<0.001) and a higher frequency of carotid plaques (OR: 3.12, p=0.04) 15.…”
Section: Introductionmentioning
confidence: 99%
“…There is also an increased prevalence of subclinical atherosclerosis in patients with PsA 14 15. A recent meta-analysis confirmed an increased carotid intima-media thickness (IMT) (mean difference: 0.07 mm, p<0.001) and a higher frequency of carotid plaques (OR: 3.12, p=0.04) 15. Carotid atherosclerosis has been shown to improve risk prediction for incident CVD over what was achieved by a model with Framingham risk factors alone in the general population,16 as well as improving CV risk stratification in patients with PsA 14 17.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with PsA have an increased risk of subclinical atherosclerosis910. A recent meta-analysis revealed that PsA patients had an higher frequency of having carotid plaque compared with healthy controls [odds ratio (OR): 3.12]10.…”
mentioning
confidence: 99%
“…Patients with PsA have an increased risk of subclinical atherosclerosis910. A recent meta-analysis revealed that PsA patients had an higher frequency of having carotid plaque compared with healthy controls [odds ratio (OR): 3.12]10. Although studies on the areal BMD (aBMD) by dual-energy X-ray absorptiometry (DXA) yielded conflicting results111213, two recent studies evaluated the bone quality of distal radius using high-resolution peripheral quantitative computed tomography (HR-pQCT) and found compromised volumetric BMD (vBMD) and microstructure in PsA patients1415.…”
mentioning
confidence: 99%